Postharvest quality and prolong storage time of atemoya (Annona squamosa x A. cherimola hybrids) fruit: coating with D-limonene nanoemulsion edible film. Issue 1 (31st December 2023) - Hou, Chih-Yao; Hazeena, Sulfath Hakkim; Li, Pin-Xian; Hsieh, Shu-Ling; Hsieh, Chang-Wei; Chen, Min-Hung; Shih, Ming-Kuei; Yu, Meng-Chieh; Liang, Yu-Shen
ABSTRACT: Atemoya (Annona squamosa x A. cherimola hybrid) is a typical climacteric fruit that has a high respiration rate after harvest, short storage life, and is highly susceptible to fruit cracking and rot. Therefore, this study was intended to apply D-limonene nanoemulsion coating on fruit to prolong the storage life, reduce spoilage, and facilitate the expansion of the market. Green mature atemoya fruit coated with different concentrations of D-limonene nanoemulsion (0.25%, 0.5%, 1.0%, 1.5%, and control) was stored in a 14°C refrigerator for relevant analysis and investigation. The results showed that the use of 0.25% D-limonene nanoemulsion inhibited the browning on the fruit surface, and reduced physiological metabolisms. The browning phenomenon on the fruit surface increased as the D-limonene concentration ratio increases. Since the high concentration caused damage to the peel cells, 0.25% D-limonene was chosen as optimum for atemoya coating. The fruit of atemoya maintained green peel color (L × 28.6, a × 6.63, b × 12.3) after storage at 14°C for 21 days with 0.25% D-limonene nanoemulsion coating. At the same time, after 0.2% D-limonene nanoemulsion coating, the weight loss rate was about % less than that of the control group (0.25% treatment was 11.3%; control was 14.2%) and high pectin content (0.25% treatment was 16.9 mg AGA g −1 AIS −1 ; control was 9.89 mg AGA g −1 AIS −1 ). Coating of D-limonene nanoemulsion can reduce the physiological response of atemoya fruits after harvesting, prolong the storage time, and increase the feasibility of their export. From the experimental results, D-limonene showed the potential to be widely used in fruit preservation agents in the future.